Amaranth Seeds and Products – The Source of Bioactive Compounds - Ogrodowska Dorota; Zadernowski Ryszard; Czaplicki Sylwester; Derewiaka Dorota; Wronowska Beata (Polish Journal of Food and Nutrition Sciences)
In recent years, new products obtained from amaranth seeds have entered the food market including expanded “popping” seeds and flakes. Lipids and biologically-active substances dissolved in these products are susceptible to changes. Additionally, due to the fact that fat quality has high dietary importance, there is a need to conduct detailed quality and quantity studies on the lipid composition of Amaranthus cruentus.